2013
DOI: 10.1097/brs.0b013e3182a54f00
|View full text |Cite
|
Sign up to set email alerts
|

Ossification of the Posterior Longitudinal Ligament in Not Only the Cervical Spine, but Also Other Spinal Regions

Abstract: This study demonstrated that more than half of the patients with cervical OPLL had coexisting OPLL in the thoracic and/or lumbar spine. We strongly recommend computed tomographic analysis of the whole spine for patients with radiographical evidence of OPLL in the cervical spine for the early detection of additional sites of ossification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
69
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 81 publications
(72 citation statements)
references
References 21 publications
3
69
0
Order By: Relevance
“…Kappa values 0.00–0.20 were considered to indicate slight agreement; 0.21–0.40, fair agreement; 0.41–0.60, moderate agreement; 0.61–0.80, substantial agreement; and 0.811.00, almost perfect agreement [17]. Therefore, this finding indicates substantial agreement and consistency with the results of the previous study [9]. We also evaluated the degree of OPLL occupying the cervical spinal canal, with classification of the canal narrowing ratio (CNR) [18] at the most compressed segment defined as follows: Grade 1, 0% < CNR ≤ 25%; Grade 2, 25% < CNR ≤ 50%; Grade 3, 50% < CNR ≤ 75%; and Grade 4, CNR > 75%.…”
Section: Methodssupporting
confidence: 84%
See 4 more Smart Citations
“…Kappa values 0.00–0.20 were considered to indicate slight agreement; 0.21–0.40, fair agreement; 0.41–0.60, moderate agreement; 0.61–0.80, substantial agreement; and 0.811.00, almost perfect agreement [17]. Therefore, this finding indicates substantial agreement and consistency with the results of the previous study [9]. We also evaluated the degree of OPLL occupying the cervical spinal canal, with classification of the canal narrowing ratio (CNR) [18] at the most compressed segment defined as follows: Grade 1, 0% < CNR ≤ 25%; Grade 2, 25% < CNR ≤ 50%; Grade 3, 50% < CNR ≤ 75%; and Grade 4, CNR > 75%.…”
Section: Methodssupporting
confidence: 84%
“…This finding is consistent with evidence that female patients tend to have OPLL in the thoracic spine—the area of the spine in which the number of vertebral and intervertebral levels is greatest—and indicates that hormonal factors could affect the development of OPLL in the whole spine. Although the details of why patients with multiple ossified lesions are predominantly female remain unclear, several studies have suggested possible mechanisms linking sex and hyperostosis [9,2123]. Serum estrogen level has been shown to correlate with the onset and extension of ossified lesions, and estrogen is thought to stimulate osteoblast-like cells with the aid of trophic factors [9,21,22].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations